1970
DOI: 10.1021/jm00296a021
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral agents. I. Bicyclo[2.2.2]octan- and -oct-2-enamines

Abstract: Yol. ¡:i 1 .(i-dibi'oinohexane in 100 ml of THF maintained tinder X2 al rtz. -0°was added dropwise over 0.7.5 hr a solution of 42..5 ml of 20') PhLi solution (70:30 C«H6-Et20). The resultant solution was allowed to mine to room temperatnre over a 2l)-br period. Hit) (.70 ml) was slowly added to destroy the unreaeted PhLi.The two phases were separated, the aqueous phase was discarded and the organic phase was washed ill.(haml dried iCaChi. The solvent, was evaporated tinder reduced pressure and the residue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…and diethyl malonate (the first method was described earlier: Scheme 1 [7]). It was shown that 18a reacted with diethyl malonate in MeCN in the presence of MgCl 2 / Et 3 N. After treatment of the reaction mixture with p-TsOH in toluene, CF 3 -pyrone 2 was isolated (67%) (Scheme 5) [13].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…and diethyl malonate (the first method was described earlier: Scheme 1 [7]). It was shown that 18a reacted with diethyl malonate in MeCN in the presence of MgCl 2 / Et 3 N. After treatment of the reaction mixture with p-TsOH in toluene, CF 3 -pyrone 2 was isolated (67%) (Scheme 5) [13].…”
Section: Methodsmentioning
confidence: 99%
“…The first representative of 6-CF 3 -2-pyrones, ethyl 6-(trifluoromethyl)-2H-pyran-2-one-3-carboxylate 2, was obtained (10%) by treatment of diethyl ethoxymethylenemalonate 1 with trifluoroacetone in the presence of EtONa (Scheme 1) [7]. This reaction is the only described example when trifluoroacetone was used as an active methylene compound for the preparation of a 6-CF 3 -2-pyrone.…”
Section: Reaction Of Diethyl Ethoxymethylenemalonate With Trifluoroacmentioning
confidence: 99%
See 3 more Smart Citations